Revolusi Industri 4. 0 Berbasis Revolusi Mental - Hendra Suwardana (Industrial Engineering, Engineering of Faculty, Universitas Kadiri, 2018)
The industrial revolution has changed the way people work into automation / digitalization through innovations. Industry players play an active role as an organizational entity that has a vision of achieving profits. The industrial revolution is based on a mental revolution in which in this paradigm there are major changes in the mental structure that is built on three things, namely the way of thinking, believing and how to behave. Mental revolution is balanced with an education system and increased self-potential through training to respond to the era of globalization with the character of the industrial revolution 4.0 where in this era new literacy is needed by using data analysis thoroughly and making conclusions to be related to communication skills, collaboration, critical thinking, creative and innovative. The existence of the industrial revolution provides benefits in increasing savings and minimizing consumption because in this case there are opportunities for e-commerce and digital economic developers for industry players. Synthesis of the industrial revolution 4.0 will give birth to a prosperous society in development, while the mental revolution breeds qualified and superior humans. Revolusi industri telah mengubah cara kerja manusia menjadi otomatisasi/digitalisasi melalui inovasi-inovasi. Para pelaku industri berperan secara aktif sebagai entitas organisasi yang memiliki visi dalam meraih keuntungan. Revolusi industri berjalan dengan dilandasi revolusi mental dimana dalam paradigma ini terdapat perubahan besar dalam struktur mental yang terbangun atas tiga hal yaitu cara berpikir, meyakini dan cara bersikap. Revolusi mental diimbangi dengan sistem pendidikan dan peningkatan potensi diri melalui pelatihan untuk menyikapi era globalisasi yang berwatak revolusi industri 4.0 dimana dalam era ini diperlukan literasi baru dengan menggunakan analisa data secara menyeluruh serta membuat konklusi agar terkait dengan kemampuan komunikasi, kolaborasi, berpikir kritis, kreatif dan inovatif. Adanya revolusi industri memberikan keuntungan dalam meningkatkan tabungan dan meminimalkan konsumsi karena dalam hal ini terdapat peluang e-commerce dan pengembang ekonomi digital bagi para pelaku industri. Sintesis revolusi industri 4.0 akan melahirkan masyarakat sejahtera dalam pembangunan, sedangkan revolusi mental melahirkan manusia yang berkualitas dan unggul.